Mothers choose a snack for their 2–3-year-old children based on different health perceptions. (December 2021) - Damen, Femke W.M.; Luning, Pieternel A.; Fogliano, Vincenzo; Steenbekkers, Bea L.P.A.
Highlights: All mothers reported health as a consideration in snack providing to their children. Three types of mothers were defined according to their healthiness perception. "Product mothers" related healthiness of a snack to the intrinsic product properties. "Balancing mothers" related healthiness of a snack to the overall diet. The "not that important mothers" thought healthiness of a snack is not that relevant. Abstract: Healthiness is an often-reported consideration related to the snack choice of mothers for their children. Mothers' perceived healthiness of a certain snack could be diverse and different compared to the actual nutritional healthiness of that specific snack. Diary studies and in-depth interviews with 22 Dutch mothers were conducted. During the interviews, four different types of cookies were presented and discussed. Data from the diaries and the interviews were transcribed, coded and grouped and presented in tables. All mothers mentioned health as a consideration while providing snacks both in the interviews and in the diaries. For more than two-thirds of the mothers, health was the most important consideration. Three types of mothers were defined according to healthiness perception: "product mothers", who related the healthiness of a snack to the intrinsic product properties, the "balancing mothers" who related the healthiness of the snack to the whole diet and the context, and the "not that important mothers", for whom the healthiness of a snack was not that relevant because the healthy foods were already eaten during the main meals. The results of this study could be used for efficient communication to help mothers meet children's dietary requirements and they could be relevant for the design of new snack products.